Preparation method of graphitized gradient carbon-coated carbon aerogel wave-absorbing material

By adsorbing ZIF-8 nanocubes on the surface of graphene aerogel and performing one-step pyrolysis, core-shell carbon@carbon composite aerogels with different degrees of graphitization are prepared, which solves the tedious steps and inconsistent impedance of existing methods. Matching problem, achieving efficient electromagnetic wave absorption in a wide frequency band.

CN119350057AInactive Publication Date: 2025-01-24ZHONGBEI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411226076.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing methods have complicated steps to prepare core-shell carbon/carbon composites and have mismatched impedances, making it difficult to achieve effective broadband electromagnetic absorption.

Method used

By adsorbing ZIF-8 nanocubes on the surface of graphene aerogel and through a one-step pyrolysis process, core-shell carbon@carbon composite aerogels with different degrees of graphitization are prepared to form an amorphous carbon layer with low conductivity. , improve impedance matching characteristics.

Benefits of technology

It significantly improves the impedance matching characteristics of composite gas gels and the absorption of electromagnetic waves, realizes the high -efficiency electromagnetic wave absorption of the broadband band, and avoids the environmental pollution and high cost of the template method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350057A_ABST
    Figure CN119350057A_ABST
Patent Text Reader

Abstract

The invention aims to provide a preparation method of a carbon-at-carbon aerogel wave-absorbing material with graphitization gradient, and belongs to the technical field of electromagnetic wave absorbing materials, ZIF-8 nanocubes are adsorbed on the surface of graphene aerogel, and core-shell carbon-at-carbon composite aerogel with graphitization degree difference is obtained through a one-step pyrolysis process. The core-shell carbon-at-carbon composite aerogel wave-absorbing material obtained by the method can effectively avoid the problems of environmental pollution and high cost caused by use of a template, and the carbon shell with different graphitization degrees can also optimize the impedance matching characteristic of the whole material so as to improve the wave-absorbing performance. The material prepared by the method is used for preparing a light and efficient electromagnetic wave absorbing coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic wave absorbing materials, and in particular relates to a method for preparing a graphitized gradient carbon@carbon aerogel absorbing material. Background Art

[0002] The rapid development of wireless communication technology has led to a sharp increase in the number of various types of highly integrated and high-power electronic devices, resulting in increasingly prominent electromagnetic interference and electromagnetic pollution problems. As a characteristic functional medium that can interact with electric or magnetic field branches, electromagnetic wave absorbing materials have a wide range of applications in the fields of military stealth and electromagnetic compatibility. Among the many electromagnetic wave absorbing materials (such as magnetic metals / ferrites, metal oxides / sulfides, conductive polymers, etc.), carbon materials have been considered as candidates for high-performance electromagnetic wave absorbing materials due to their adjustable dielectric properties, low density, high chemical stability and designable microstructures. However, studies have found that carbon materials with high graphitization (for example, graphene, carbon nanotubes and graphite, etc.) often have poor impedance matching due to their ultra-high dielectric values, resulting in poor electromagnetic wave absorption. Although carbon materials with medium / low graphitization have good impedance matching characteristics, it is difficult to achieve effective broadband electromagnetic absorption due to weak electromagnetic loss intensity. At present, a large number of research results have shown that optimizing the electromagnetic parameters of carbon materials through structural design strategies can improve the overall impedance matching and attenuation characteristics of the material. This has become a new solution to the problem and has attracted widespread attention from researchers. Core-shell nanocomposites can choose whether to be the core or the shell according to the characteristics of different components. This feature can significantly optimize the impedance matching characteristics and improve the electromagnetic wave attenuation ability. However, the preparation of these core-shell structures mostly relies on cumbersome template methods. These processes are very costly and harmful to the environment, limiting their further widespread use. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a graphitized gradient carbon@carbon aerogel absorbing material to solve the technical problems of complicated steps and impedance mismatch in the preparation of core-shell carbon / carbon composite materials by existing methods.

[0004] The present invention adopts the following technical solution: The present invention adsorbs ZIF-8 nanocubes on the surface of graphene aerogel, and obtains core-shell carbon@carbon composite aerogels with different graphitization degrees through a one-step pyrolysis process. The specific steps are as follows: In the first step, graphene oxide is dispersed in ultrapure water by ultrasonication to obtain a graphene oxide suspension; In the second step, the graphene oxide suspension obtained in the first step is transferred to a Teflon reactor and sealed for reaction. During the hydrothermal reaction, the graphene oxide realizes orderly π-π stacking connection and assembles into three-dimensional graphene oxide black elastic columns. The third step is to move the three-dimensional graphene oxide black elastic column obtained in the second step into a constant temperature refrigerator for freezing, and then freeze-dry in vacuum to obtain reduced graphene oxide gel rGA; Step 4: dissolving hexadecyltrimethylammonium bromide (CTAB) in deionized water to obtain a clear solution; Step 5: Zn(NO 3 ) 2 •6H 2 O is added to the solution obtained in step 4, and stirred to completely dissolve it to obtain a clear solution; Step 6, slowly inject the solution obtained in step 5 into the bottle containing rGA, slowly shake it, let it stand, then slowly add the 2-methylimidazole aqueous solution, continue to stand, filter the product, wash it with ethanol, and vacuum freeze-dry it to obtain a black columnar product; Step 7: Place the black columnar product obtained in step 6 into a magnetic boat, transfer it to a tube furnace, and perform high-temperature calcination under an Ar atmosphere to finally obtain a black product; In the eighth step, the black product obtained in the seventh step is placed in a beaker, and is soaked in a hydrochloric acid solution, filtered, washed with deionized water and industrial ethanol for several times, and dried to obtain the final product.

[0005] Furthermore, in the first step, the amount of graphene oxide used is 0.08-0.12 g, the amount of ultrapure water used is 195-205 mL, and the ultrasonic time is 3 h.

[0006] Furthermore, in the second step, the volume of the Teflon reactor is 50 mL, the hydrothermal reaction temperature is 180° C., and the reaction time is 24 h.

[0007] Furthermore, in the third step, the freezing temperature is -50°C and the freezing time is 12 hours.

[0008] Furthermore, in the fourth step, the amount of CTAB used is 4-6 mg, and the amount of deionized water used is 10-11 mL.

[0009] Further, in the fifth step, the Zn(NO 3 ) 2 •6H 2 The amount of O used was 70-74 mg and the stirring time was 30 min.

[0010] Furthermore, in the sixth step, the amount of rGA used is 1.6-2 mg, the standing time is 15 h, the concentration of the 2-methylimidazole aqueous solution is 1 mg / mL, and the standing time is continued for 3 h.

[0011] Furthermore, the heating rate of the high temperature calcination in the seventh step is 5°C / min, the calcination temperature is 700°C, and the calcination time is 3h.

[0012] Furthermore, the concentration of the hydrochloric acid solution in the eighth step is 0.5 mol / L, and the immersion time is 12 h.

[0013] Furthermore, in the eighth step, the drying temperature is 40° C. and the drying time is 24 hours.

[0014] The graphitized gradient carbon@carbon aerogel absorbing material formed by the method provided by the present invention is mainly that ZIF-8 crystals are restrictedly grown on a graphene oxide substrate through a strong coupling effect, and a dense carbon coating layer is generated on the surface of the reduced graphene oxide aerogel substrate after in-situ thermal conversion, and the carbon shell converted from ZIF-8 is an amorphous carbon layer with low electrical conductivity, which suppresses the skin current of the reduced graphene oxide aerogel with a high degree of graphitization in the inner layer, and significantly improves the impedance matching characteristics of the composite aerogel.

[0015] The carbon@carbon composite aerogel with graphitization gradient prepared by the present invention can be used in an electromagnetic wave absorber. The absorber includes a carbon@carbon aerogel electromagnetic wave receiving material with graphitization gradient and paraffin. The mass percentage of the carbon@carbon aerogel electromagnetic wave receiving material with graphitization gradient in the absorber can be adjusted according to actual needs.

[0016] Preferably, the mass fraction of the graphitized gradient carbon@carbon aerogel electromagnetic wave receiving material in the absorber is 8%. At this filler ratio, the frequency range in which the reflection loss intensity is less than -10 dB is 3.1-18.0 GHz.

[0017] The beneficial effects of the present invention are: (1) The prepared graphitized gradient carbon@carbon aerogel effectively avoids the problems of environmental pollution and high cost caused by the use of templates, and the prepared composite aerogel has good stability.

[0018] (2) The prepared amorphous carbon layer with a low degree of graphitization and a graphitized gradient carbon@carbon aerogel outer layer has a low electrical conductivity and significantly improves the impedance matching characteristics of the composite material.

[0019] (3) The absorber has excellent wave absorption performance and a wide effective absorption bandwidth. The prepared absorber is thin in thickness, light in weight, and has high absorption intensity. It has broad application prospects in the fields of electromagnetic wave absorption in the communication technology field, prevention of electromagnetic leakage, and electromagnetic protection of high-precision instruments.

[0020] The graphitized gradient carbon@carbon aerogel prepared by the present invention presents a unique nested network structure. This result shows that densely coating the heterogeneous layer on the surface of the aerogel can indeed improve the stability of the aerogel. And the impedance matching characteristics are excellent. The maximum reflection loss can reach -28.6 dB. When the thickness of the absorber is 1.3 mm, the bandwidth in which the reflection loss is less than -10dB can reach about 5.1 GHz, ranging from 12.9 to 18.0 GHz.

[0021] In summary, the present invention prepares a graphitized gradient carbon@carbon aerogel electromagnetic wave absorption material, which has good impedance matching characteristics. This graphitized gradient carbon@carbon aerogel composite material obtained through clever design not only effectively avoids the problems of environmental pollution and high cost caused by the use of templates, but also the amorphous carbon layer with low graphitization degree coated on the outer layer of the prepared composite material can suppress the skin current of the inner layer of graphene oxide aerogel with high graphitization degree, significantly improving the impedance matching characteristics of the composite material. It has broad application prospects in the field of electromagnetic absorption.

[0022] The material prepared by the invention is used for making a light and efficient wave absorbing coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of the graphitized gradient carbon@carbon aerogel absorbing material prepared in Example 1; Figure 2 The XRD graphs of the graphitized gradient carbon@carbon aerogel absorbing material and the comparative sample prepared in Example 1, wherein curve a is the XRD of the comparative sample; curve b is the XRD of the graphitized gradient carbon@carbon aerogel absorbing material; Figure 3 The Raman spectra of the graphitized gradient carbon@carbon aerogel absorbing material and the comparative sample prepared in Example 1, wherein curve a is the Raman spectrum of the comparative sample; curve b is the Raman spectrum of the graphitized gradient carbon@carbon aerogel absorbing material; Figure 4 The graph is a real part curve of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorbing material and the comparative sample prepared in Example 1, wherein curve a is the real part curve of the dielectric constant of the comparative sample; curve b is the real part curve of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorbing material; Figure 5 The graph is a graph of the imaginary part of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorbing material and the comparative sample prepared in Example 1, wherein curve a is the imaginary part of the dielectric constant of the comparative sample; curve b is the imaginary part of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorbing material; Figure 6The wave impedance curves of the graphitized gradient carbon@carbon aerogel absorbing material and the comparative sample prepared in Example 1, a is the wave impedance curve of the comparative sample; b is the wave impedance curve of the graphitized gradient carbon@carbon aerogel absorbing material; Figure 7 Three-dimensional and two-dimensional graphs of the reflection loss of the graphitized gradient carbon@carbon aerogel absorber prepared in Example 1. DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1 A method for preparing a graphitized gradient carbon@carbon aerogel absorbing material comprises the following steps: In the first step, 0.1 g of graphene oxide was dispersed in 200 mL of ultrapure water and ultrasonicated for 3 h to obtain a graphene oxide suspension; In the second step, the graphene oxide suspension was transferred to a 50 mL Teflon reactor and sealed at 180°C for 24 h. During the hydrothermal reaction, the graphene oxide achieved orderly π-π stacking connections and assembled into three-dimensional graphene oxide black elastic columns. In the third step, the graphene black elastic column was transferred to a -50°C constant temperature refrigerator and frozen for 12 h, and then vacuum-freeze-dried to obtain reduced graphene oxide gel (rGA); Step 4: Dissolve 5 mg of hexadecyltrimethylammonium bromide (CTAB) in 10.5 mL of deionized water to obtain a clear solution. Step 5: 72 mg Zn(NO 3 ) 2 •6H 2 O was added to the solution obtained in the fourth step, and stirred for 30 min to completely dissolve it to obtain a clear solution; Step 6: slowly inject the solution obtained in step 5 into the bottle containing 1.8 mg rGA obtained in step 3, shake slowly, let stand, then slowly add 2-methylimidazole aqueous solution (1 mg / mL), continue to stand for 3 h, filter the product, wash with ethanol, and vacuum freeze-dry to obtain a black columnar product; Step 7: Place the product obtained in step 6 into a magnetic boat, transfer it to a tube furnace, and heat it from room temperature to 700°C in an Ar atmosphere at a heating rate of 5°C / min for 3 h. Perform high-temperature calcination to obtain a black product. In the eighth step, the product obtained in the seventh step was placed in a beaker and soaked in 0.5 mol / L hydrochloric acid solution for 12 h to remove the metallic zinc species in the sample, filtered, washed with deionized and industrial ethanol water several times, and dried at 40°C for 24 h to obtain the final product.

[0026] Example 2 A method for preparing a graphitized gradient carbon@carbon aerogel absorbing material comprises the following steps: In the first step, 0.08 g of graphene oxide was dispersed in 195 mL of ultrapure water and ultrasonicated for 3 h to obtain a graphene oxide suspension; In the second step, the graphene oxide suspension was transferred to a 50 mL Teflon reactor and sealed at 180°C for 24 h. During the hydrothermal reaction, the graphene oxide achieved orderly π-π stacking connections and assembled into three-dimensional graphene oxide black elastic columns. In the third step, the graphene black elastic column was transferred to a -50°C constant temperature refrigerator and frozen for 12 h, and then vacuum-freeze-dried to obtain reduced graphene oxide gel (rGA); Step 4: Dissolve 4 mg of hexadecyltrimethylammonium bromide (CTAB) in 10 mL of deionized water to obtain a clear solution. Step 5: 70 mg Zn(NO 3 ) 2 •6H 2 O was added to the solution obtained in the fourth step, and stirred for 30 min to completely dissolve it to obtain a clear solution; Step 6: slowly inject the solution obtained in step 5 into the bottle containing 1.6 mg rGA obtained in step 3, shake slowly, let stand, then slowly add 2-methylimidazole aqueous solution (1 mg / mL), continue to stand for 3 h, filter the product, wash with ethanol, and vacuum freeze-dry to obtain a black columnar product; Step 7: Place the product obtained in step 6 into a magnetic boat, transfer it to a tube furnace, and heat it from room temperature to 700°C in an Ar atmosphere at a heating rate of 5°C / min for 3 h. Perform high-temperature calcination to obtain a black product. In the eighth step, the product obtained in the seventh step was placed in a beaker and soaked in 0.5 mol / L hydrochloric acid solution for 12 h to remove the metallic zinc species in the sample, filtered, washed with deionized and industrial ethanol water several times, and dried at 40°C for 24 h to obtain the final product.

[0027] Example 3 A method for preparing a graphitized gradient carbon@carbon aerogel absorbing material comprises the following steps: In the first step, 0.12 g of graphene oxide was dispersed in 205 mL of ultrapure water and ultrasonicated for 3 h to obtain a graphene oxide suspension; In the second step, the graphene oxide suspension was transferred to a 50 mL Teflon reactor and sealed at 180°C for 24 h. During the hydrothermal reaction, the graphene oxide achieved orderly π-π stacking connections and assembled into three-dimensional graphene oxide black elastic columns. In the third step, the graphene black elastic column was transferred to a -50°C constant temperature refrigerator and frozen for 12 h, and then vacuum-freeze-dried to obtain reduced graphene oxide gel (rGA); Step 4: 6 mg of hexadecyltrimethylammonium bromide (CTAB) was dissolved in 11 mL of deionized water to obtain a clear solution; Step 5: 74 mg Zn(NO 3 ) 2 •6H 2 O was added to the solution obtained in the fourth step, and stirred for 30 min to completely dissolve it to obtain a clear solution; Step 6: slowly inject the solution obtained in step 5 into the bottle containing 2 mg rGA obtained in step 3, shake slowly, let stand, then slowly add 2-methylimidazole aqueous solution (1 mg / mL), continue to stand for 3 h, filter the product, wash with ethanol, and vacuum freeze-dry to obtain a black columnar product; Step 7: Place the product obtained in step 6 into a magnetic boat, transfer it to a tube furnace, and heat it from room temperature to 700°C in an Ar atmosphere at a heating rate of 5°C / min for 3 h. Perform high-temperature calcination to obtain a black product. In the eighth step, the product obtained in the seventh step was placed in a beaker and soaked in 0.5 mol / L hydrochloric acid solution for 12 h to remove the metallic zinc species in the sample, filtered, washed with deionized and industrial ethanol water several times, and dried at 40°C for 24 h to obtain the final product.

[0028] Comparative Example The comparative example is the reduced graphene oxide aerogel obtained by calcining the product of the second step of Example 1 at high temperature. The calcination process is consistent with the above, that is, the heating rate is 5°C / min, the calcination temperature is 700°C, and the calcination time is 3 h.

[0029] Figure 1 This is a scanning electron microscope image of the graphitized gradient carbon@carbon aerogel absorbing material prepared in Example 1; it can be seen from the figure that the obtained graphitized gradient carbon@carbon aerogel absorbing material has a macroporous structure and a high porosity, and amorphous carbon nanoparticles are densely covered on both sides of the pore walls to form a unique nested network structure, indicating that densely coating the heterogeneous layer on the surface of the aerogel can indeed improve the stability of the aerogel.

[0030] Figure 2The XRD graphs of the carbon@carbon aerogel absorber with graphitization gradient and the comparative sample prepared in Example 1, curve a in the figure is the XRD of the comparative sample; curve b is the XRD of the carbon@carbon aerogel absorber with graphitization gradient. By comparing the X-ray diffraction standard card, it can be seen that although the carbon@carbon aerogel absorber and the comparative sample both contain the diffraction peak of graphite carbon, the position of the peak of the graphitization gradient carbon@carbon aerogel has changed slightly compared with the comparative sample, and it shifts to a small angle. This result shows that in addition to graphite carbon, amorphous carbon also exists in the carbon@carbon composite aerogel, and the graphitization degree of the carbon@carbon aerogel electromagnetic wave absorber is lower than that of the comparative sample.

[0031] Figure 3 The Raman spectra of the graphitized gradient carbon@carbon aerogel absorbing material and the comparative sample prepared in Example 1, curve a in the figure is the Raman spectrum of the comparative sample; curve b is the Raman spectrum of the graphitized gradient carbon@carbon aerogel absorbing material. It can be seen from the figure that the graphitized gradient carbon@carbon aerogel absorbing material I D / I G The value is higher than that of the comparison sample I D / I G The large value further indicates that the graphitization degree of the carbon@carbon aerogel absorber with graphitization gradient is lower than that of the control sample.

[0032] Figure 4 The graph is a real part curve of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorbing material and the comparative sample prepared in Example 1. Curve a in the graph is the real part curve of the dielectric constant of the comparative sample; curve b is the real part curve of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorbing material. It can be seen from the figure that the real part value of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorbing material is lower than the real part value of the dielectric constant of the comparative sample, because the graphitization degree of the graphitization gradient carbon@carbon aerogel absorbing material is lower than the graphitization degree of the comparative sample.

[0033] Figure 5 The graph is a graph of the imaginary part of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorber and the comparative sample prepared in Example 1. Curve a in the graph is the imaginary part of the dielectric constant of the comparative sample; curve b is the imaginary part of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorber. It can be seen from the figure that the imaginary part of the dielectric constant of the graphitized gradient carbon@carbon aerogel absorber is lower than that of the comparative sample, because the amorphous carbon layer covering the outer layer reduces the overall conductivity of the composite aerogel.

[0034] Figure 6The wave impedance curves of the graphitized gradient carbon@carbon aerogel absorbing material and the comparative sample prepared in Example 1, a is the wave impedance curve of the comparative sample; b is the wave impedance curve of the graphitized gradient carbon@carbon aerogel absorbing material. It can be seen from the figure that the wave impedance value of the graphitized gradient carbon@carbon aerogel absorbing material is higher than that of the comparative sample, indicating that the outer amorphous carbon layer can significantly improve the impedance matching characteristics of the composite aerogel as a whole.

[0035] Figure 7 The three-dimensional and two-dimensional graphs of the reflection loss of the graphitized gradient carbon@carbon aerogel absorber prepared in Example 1, where the frequency is 2.0~18.0 GHz and the thickness is 1.0~5.0 mm. It can be seen from the figure that the maximum reflection loss value of the composite aerogel is -28.6 dB at a frequency of 15.8 GHz; and when the thickness is in the range of 1.0~5.0 mm, the frequency band range in which the reflection loss is less than -10 dB is 3.1~18.0 GHz (about 15 GHz), which can achieve C-band, X-band and Ku-band coverage, indicating that the graphitized gradient carbon@carbon aerogel absorber has excellent electromagnetic wave absorption capacity.

[0036] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a graphitized gradient carbon@carbon aerogel absorbing material, characterized in that: The steps include: In the first step, graphene oxide is dispersed in ultrapure water by ultrasonication to obtain a graphene oxide suspension; In the second step, the graphene oxide suspension obtained in the first step is transferred to a Teflon reactor and sealed for reaction. During the hydrothermal reaction, the graphene oxide realizes orderly π-π stacking connection and assembles into three-dimensional graphene oxide black elastic columns. The third step is to move the three-dimensional graphene oxide black elastic column obtained in the second step into a constant temperature refrigerator for freezing, and then freeze-dry in vacuum to obtain reduced graphene oxide gel rGA; Step 4: dissolving hexadecyltrimethylammonium bromide (CTAB) in deionized water to obtain a clear solution; Step 5, adding Zn(NO3)2•6H2O to the solution obtained in step 4, stirring to completely dissolve it, and obtaining a clear solution; Step 6, slowly inject the solution obtained in step 5 into the bottle containing rGA, slowly shake it, let it stand, then slowly add the 2-methylimidazole aqueous solution, continue to stand, filter the product, wash it with ethanol, and vacuum freeze-dry it to obtain a black columnar product; Step 7: Place the black columnar product obtained in step 6 into a magnetic boat, transfer it to a tube furnace, and perform high-temperature calcination under an Ar atmosphere to finally obtain a black product; In the eighth step, the black product obtained in the seventh step is placed in a beaker, and is soaked in a hydrochloric acid solution, filtered, washed with deionized water and industrial ethanol for several times, and dried to obtain the final product.

2. The method for preparing a graphitized gradient carbon@carbon aerogel absorbing material according to claim 1, characterized in that: In the first step, the amount of graphene oxide used is 0.08-0.12 g, the amount of ultrapure water used is 195-205 mL, and the ultrasonic time is 3 h.

3. The method for preparing a graphitized gradient carbon@carbon aerogel absorbing material according to claim 1, characterized in that: In the second step, the volume of the Teflon reactor is 50 mL, the hydrothermal reaction temperature is 180° C., and the reaction time is 24 h.

4. The method for preparing a graphitized gradient carbon@carbon aerogel absorbing material according to claim 1, characterized in that: The freezing temperature in the third step is -50°C and the freezing time is 12h.

5. The method for preparing a graphitized gradient carbon@carbon aerogel absorbing material according to claim 1, characterized in that: In the fourth step, the amount of CTAB used is 4-6 mg, and the amount of deionized water used is 10-11 mL.

6. The method for preparing a graphitized gradient carbon@carbon aerogel absorbing material according to claim 1, characterized in that: In the fifth step, the amount of Zn(NO3)2•6H2O used is 70-74 mg, and the stirring time is 30 min.

7. The method for preparing a graphitized gradient carbon@carbon aerogel absorbing material according to claim 1, characterized in that: In the sixth step, the amount of rGA used is 1.6-2 mg, the standing time is 15 h, the concentration of the 2-methylimidazole aqueous solution is 1 mg / mL, and the standing time is continued for 3 h.

8. The method for preparing a graphitized gradient carbon@carbon aerogel absorbing material according to claim 1, characterized in that: The heating rate of the high-temperature calcination in the seventh step is 5°C / min, the calcination temperature is 700°C, and the calcination time is 3h.

9. The method for preparing a graphitized gradient carbon@carbon aerogel absorbing material according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in the eighth step is 0.5 mol / L, and the soaking time is 12 h.

10. The method for preparing a graphitized gradient carbon@carbon aerogel absorbing material according to claim 1, characterized in that: The drying temperature in the eighth step is 40° C. and the drying time is 24 h.

Citation Information

Patent Citations

  • Preparation method and application of boron and nitrogen co-doped graphene carbon aerogel wave-absorbing material

    CN118495951A